Distinct clinical pattern of colorectal cancer patients with POLE mutations: A retrospective study on real-world data - Jiang, Miao; Jia, Yongliang; Han, Jinming; Shi, Jianxiang; Su, Chang; Zhang, Rui; Xing, Menglu; Jin, Shuiling; Zong, Hong (Frontiers in Genetics, 2022)
Objective: Studies have demonstrated an association between somatic POLE exonuclease domain mutations (EDMs) and the prognosis of colorectal cancer (CRC). However, the prognostic value of POLE non-EDMs remains unclear. This retrospective study aimed to explore the possible relationships between POLE mutation subtypes and CRC prognosis. Methods: The 272 CRC patients from the First Affiliated Hospital of Zhengzhou University (ZZ cohort) and 499 CRC patients from The Cancer Genome Atlas database (TCGA cohort) were retrospectively collected. The cases were divided into subgroups based on POLE mutation sites and microsatellite instability (MSI) status. The continuous variables were compared among three subgroups with Kruskal-Wallis tests. Pairwise comparisons between three groups were performed by Bonferroni correction method, and adjusted P <0.05 was considered statistically significant. The categorical variables were compared with Chi-square test and Fisher's exact test. The Kaplan - Meier curves and Cox regression models were conducted to evaluate prognostic values of POLE mutations. Results: In the ZZ cohort, POLE EDMs (2.6%) were significantly associated with younger age (P=0.018) and localized in the left colon (P=0.001). POLE non-EDMs were significantly associated with MSI-high status (P<0.001) and localization in the right colon (P=0.001). In the TCGA cohort, the tumor mutation burden (TMB) of both POLE EDM tumors (P<0.001) and POLE non-EDM tumors (P<0.001) was significantly higher than that of POLE wild-type (WT) tumors. A similar trend was observed in the ZZ cohort, although there were no significant differences. In the ZZ cohort, the POLE EDM group had higher progression-free survival (PFS) (P=0.002) and overall survival (OS) (P=0.042) than the POLE non-EDM group and POLE WT group. We also report one CRC patient harboring a germline POLE mutation who received camrelizumab and exhibited long-term stable disease. Conclusions: Both POLE-EDMs and POLE non-EDMs were associated with significantly increased TMB in CRC and may be biomarkers for CRC treatment and prognosis. Current evidence does not support an effect of POLE non-EDMs on PFS and OS. A significant association between POLE EDMs and improved PFS and OS may exist, but future studies with larger sample sizes are needed. Entire coding region of the POLE gene should be screened.